Transition versus Continuous Slope Walking: Adaptation to Change Center of Mass Velocity in Young Men - Yoon No Gregory Hong; Jinkyu Lee; Choongsoo S. Shin (Applied Bionics and Biomechanics)
During continuous uphill walking (UW) or downhill walking, human locomotion is modified to counteract the gravitational force, aiding or impeding the body’s forward momentum, respectively. This study aimed at investigating the center of mass (COM) and center of pressure (COP) velocities and their relative distance during the transition from uphill to downhill walking (UDW) to determine whether locomotor adjustments differ between UDW and UW. Fourteen participants walked on a triangular slope and a continuous upslope of 15°. The kinematics and COPs were obtained using a force plate and a motion capture system. The vertical velocity of the COM in the propulsion phase, the horizontal distance between the COM and COP at initial contact, and the duration of the subphases significantly differed between UDW and UW (all p<0.05). Compared with the results of UW, longer durations and the deeper downward moving COM in the propulsion phase were observed during UDW (all p<0.05). Additionally, a shorter horizontal distance between the COM and COP at initial contact was associated with a slower vertical COM velocity in the propulsion phase during UDW. The reduced velocity is likely a gait alteration to decrease the forward momentum of the body during UDW.